2010
DOI: 10.1021/es1007609
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Phase, And Temporal Distributions of Perfluorooctane Sulfonate (PFOS) and Perfluorooctanoate (PFOA) in Tokyo Bay, Japan

Abstract: The spatial distribution, partitioning, and time trends of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) were investigated in the water column and bottom sediment of Tokyo Bay, Japan, during 2004-2006. A total of 480 water and 60 sediment samples obtained by regular 20-station samplings ascertained the three-dimensional distributions of these compounds and changes in the seawater structure in the whole bay. The median of volume-based average water-borne concentrations of PFOS and PFOA was 3.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 25 publications
3
23
2
Order By: Relevance
“…In the present study, maximum concentrations of PFOS (0.52 ng/L) and PFOA (2.3 ng/L) were several orders of magnitude less than those measured in Tokyo Bay, Japan (0.78-17 and 2.7-63 ng/L) and the Korea coast (4.11-450 and 2.95-68.6 ng/L) Sakurai et al 2010). Although PFOS and PFOA were the predominant Table 1 Quality assurance of 12 target PFCs including limit of quantification (LOQ), method detection limit (MDL) and matrix spike recovery (MSR) for water, sediment and soil (Table 2).…”
Section: Resultscontrasting
confidence: 70%
“…In the present study, maximum concentrations of PFOS (0.52 ng/L) and PFOA (2.3 ng/L) were several orders of magnitude less than those measured in Tokyo Bay, Japan (0.78-17 and 2.7-63 ng/L) and the Korea coast (4.11-450 and 2.95-68.6 ng/L) Sakurai et al 2010). Although PFOS and PFOA were the predominant Table 1 Quality assurance of 12 target PFCs including limit of quantification (LOQ), method detection limit (MDL) and matrix spike recovery (MSR) for water, sediment and soil (Table 2).…”
Section: Resultscontrasting
confidence: 70%
“…Concentrations of PFOS and PFOA were either comparable to or less than those detected in coastal waters of South Korea Rostkowski et al, 2006), Yodo River Basin, Japan (Lein et al, 2008) and various river and coastal waters in Brazil (Quinete et al, 2009). Concentrations of PFOS and PFOA measured in this study were similar to those reported for Tokyo Bay, Japan (Sakurai et al, 2010;Yamashita et al, 2004). In the present study, the maximal concentrations of PFOS (30.9 ng/l) and PFOA (81.7 ng/ l) were measured in Liaodong Bay, which were less than the greatest concentrations of PFOS (123 ng/l) and PFOA (2600 ng/l) measured in the Yodo River Basin, which is one of the most polluted rivers in Japan.…”
supporting
confidence: 89%
“…For the Yellow Sea (0.89 to 14 ng/L) and Yangtze River estuary, the PFOA concentrations (0.98 to 6.9 ng/L) were comparable to those for the coastal areas of Hong Kong (0.67 to 5.5 ng/L), though these were higher than those for the eastern and southern Chinese coasts (0.04 to 1.5 ng/L) (Cai et al, 2012b) and the South China Sea (0.16 to 0.42 ng/L) (Yamashita et al, 2005). As compared to other coastal areas globally, the PFOA concentrations in the Bohai Sea water were similar to those of the Tokyo Bay water (2.7 to 63 ng/L), which is a semiclosed bay in Japan (Sakurai et al, 2010). The PFOA concentrations in the waters of the Yellow Sea and Yangtze River estuary were similar to those in the Baltic Sea (0.25 to 4.45 ng/L) , but higher than those in the waters of the North Sea (b 0.2 to 2.43 ng/L) and coastal Norway (0.07 to 0.35 ng/L) .…”
Section: Comparison Of Pfas Concentrations In Gaseous and Dissolved Pmentioning
confidence: 65%